Possible application of circulating free tumor DNA in non-small cell lung cancer patients - Karachaliou, Niki; Sosa, Aaron E.; Molina, Miguel Angel; Ruiz, Margarita Centelles; Rosell, Rafael (Journal of Thoracic Disease, 2017)
Liquid biopsies have been heralded as a game changer in cancer management. Blood tests offer a minimally invasive, safe and sensitive complementary (or even alternative) approach for tissue biopsies. With lung cancer being the second most commonly diagnosed cancer and the leading cause of cancer deaths worldwide, due to the limitations of tissue sampling, liquid biopsies must urgently materialize in the clinic. In this short review, we will present the current applications of cell-free DNA (cfDNA) in lung cancer management, emphasizing on our own experience and previous work. We will also shortly comment on the challenges and need for a coordinated collaboration combining disciplines and sectors (from academia to health economies) in order to accelerate liquid biopsy development in lung cancer and other cancers.